VD_FINDINFO Jug / 2012 / 107 vom 15. Dezember 2011 - VD Tribunal cantonal (2011)
DIFFAMATION, SURSIS À L'EXÉCUTION DE LA PEINE, AMENDE | 106 CP, 173 ch. 1 CP, 34 CP, 42 al. 1 CP, 42 ch. 4 CP, 44 al. 1 CP, 47 CP, 50 CP